From structure to therapy: the critical influence of cartilaginous endplates and microvascular network on intervertebral disc degeneration - Yu Sun; Zhaoyong Li; Jiahao Duan; Enxu Liu; Lei Yang; Fei Sun; Long Chen; Shaofeng Yang (Frontiers in Bioengineering and Biotechnology)
The intervertebral disc (IVD) is the largest avascular structure in the human body. The cartilaginous endplate (CEP) is a layer of translucent cartilage located at the upper and lower edges of the vertebral bodies. On one hand, CEPs endure pressure from within the IVD and the tensile and shear forces of the annulus fibrosus, promoting uniform distribution of compressive loads on the vertebral bodies. On the other hand, microvascular diffusion channels within the CEP serve as the primary routes for nutrient supply to the IVD and the transport of metabolic waste. Degenerated CEP, characterized by increased stiffness, decreased permeability, and reduced water content, impairs substance transport and mechanical response within the IVD, ultimately leading to intervertebral disc degeneration (IDD). Insufficient nutrition of the IVD has long been considered the initiating factor of IDD, with CEP degeneration regarded as an early contributing factor. Additionally, CEP degeneration is frequently accompanied by Modic changes, which are common manifestations in the progression of IDD. Therefore, this paper comprehensively reviews the structure and physiological functions of CEP and its role in the cascade of IDD, exploring the intrinsic relationship between CEP degeneration and Modic changes from various perspectives. Furthermore, we summarize recent potential therapeutic approaches targeting CEP to delay IDD, offering new insights into the pathological mechanisms and regenerative repair strategies for IDD.